Web applications design recovery and evolution with RE‐UWA. Issue 8 (7th September 2012) - Bernardi, Mario Luca; Cimitile, Marta; Distante, Damiano; Kienle, Holger; Di Lucca, Giuseppe; Kontogiannis, Kostas
SUMMARY This paper presents a semi‐automatic approach for the recovery and evolution of the design of existing Web applications. The proposed approach is structured in two main phases and is based on the Ubiquitous Web Applications (UWA) design framework, a methodology and a set of models and tools for the user‐centered design of multichannel context‐aware Web applications. In the first phase a representative set of the application's front‐end Web pages are analyzed to abstract the 'as‐is' design model of the application according to the UWA methodology. In the second phase, the recovered design model is evolved to define the 'to be' version of it. This evolution activity considers the up‐to‐date requirements available for the application and UWA design guidelines to identify shortcomings and opportunities of improvement in the 'as‐is' design. The reverse modeling phase exploits clustering and clone detection techniques and is supported by the RE‐UWA tool, an Eclipse IDE customized to implement the reverse engineering process defined to extract formal UWA models expressed as instances of a MOF metamodel. The forward design phase is supported by a set of UWA modeling tools that are built on top of the Eclipse Modeling Framework (EMF) and the Eclipse Graphical Modeling Framework (GMF). The proposed design recovery and evolution approach is applied to four real‐world Web applications and the obtained results are also presented in the paper. Copyright © 2012 John Wiley & Sons, Ltd.